The Control of Diagenesis and Mineral Assemblages on Brittleness of Mudstones - Du, Jiazong; Cai, Jingong; Long, Shengxiang; Gao, Bo; Feng, Dongjun; Peng, Zeyang; Zeng, Xiang (Frontiers in Earth Science, 2021)
The variation in mineral composition will affect the rock brittleness, thus the change of mineral assemblages during diagenesis has a potential control on the brittleness of mudstones. In this study, thin section, X-ray diffraction (XRD), and Scanning Electron Microscope (SEM) analyses were used to investigate compositional and microscopic features of mudstones. With the enhancement of diagenesis, three mineral assemblages were divided due to the diagenetic evolution of minerals. Quartz, feldspar, dolomite, chlorite, and illite were regarded as brittle minerals and (quartz + feldspar + dolomite + illite + chlorite)/(detrital mineral + carbonate + clay mineral) was defined as the brittleness evaluation index The mudstone brittleness changed slightly during early diagenesis but increased gradually with enhancement of diagenesis in the late diagenesis stage. Quartz and feldspar were scattered above the clay matrix and the contact of grains was limited, therefore, the contribution of detrital minerals to the brittleness was affected by the properties of clay minerals. The diagenetic transformation of clay minerals resulted in the reduction of ductile components (smectite/I-Sm and kaolinite) and increase of brittle components (illite and chlorite), leading to the enhancement of integral rigidity of the mudstones. Meanwhile, the improved crystallization of carbonate in late diagenesis stage enlarged the carbonate grains which resulted in rigid contact between grains. These results highlighted the influence of diagenesis on mudstone brittleness. Therefore, for evaluation of mudstone brittleness, attention should be paid to the diagenesis process besides mineral composition.